Evaluation of the physical-chemical quality of minimally processed Brazilian pumpkin (Cucurbita moschata) (Research, Society and Development, 2020)
The Brazilian pumpkin has peculiar and uneven characteristics in terms of its shape pattern, which is generally rustic, and a horticultural crop widely used for consumption. The objective was to evaluate the physical-chemical characteristics of minimally processed Brazilian pumpkin. Pumpkins were harvested 70 days after planting, on the Boa Esperança farm in the municipality of Teixeira-PB and transported to the Sensory Analysis laboratory of the Center for Science and Agri-food Technology of Federal University of Campina Grande, Campus de Pombal - PB, which went through minimal processing steps, where the fruits were submitted to cuts, slices and cube. The processed fruits were placed in expanded polystyrene trays wrapped with PVC film (12 µm) and stored in a refrigerated vertical display at 3 ± 1 ° C and 78 ± 5% RH for 12 days. The physical-chemical analyzes were carried out at the Chemistry, Biochemistry and Food Analysis Laboratory of the CCTA, using a completely randomized design, in the 2x7 factorial scheme, where factor 1 corresponds to the types of cuts and factor 2 to the storage times with 5 repetitions per treatment. From the results it was possible to observe that the cuts, slice and cube, obtained low fresh weight loss along with reduced levels of ascorbic acid, phenolic compounds, flavonoids and anthocyanins. Regarding the commercial aspect, dicing resulted in better uniformity. The use of cold and covering with polyvinyl chloride (PVC) contributed for the cuts, slice and cube, to maintain a good state of conservation.